Serum lactic acid level predicts poor myocardial perfusion and in-hospital outcomes in patients undergoing primary percutaneous coronary intervention. (14th October 2021) - Liu, M Y; Dai, C F; Chen, Z W; Qian, J Y; Ge, J B
Abstract: Background: Elevated serum lactic acid level is associated with poor outcomes in patients with critical diseases like shock. However, the clinical implication of this biomarker in patients with acute myocardial infarction remains unclear. Purpose: We aimed to explore the predictive power of serum lactic acid level on admission for in-hospital outcomes in patients with acute myocardial infarction undergoing primary percutaneous coronary intervention (pPCI). Methods: Consecutive patients undergoing pPCI with available data on serum lactid acid level were evaluated for eligbility in this retrospective cohort study. The primary outcome was all-cause death during hospitalization. Enzymatic infarct size and major adverse cardiovascular events (MACE, defined as a combination of all-cause death, recurrent myocardial infarction, and unplanned repeated revascularization) were considered secondary outcomes. Independent preditors of in-hospital death were determined by multiple logisic regression analysis. Odds ratio (OR) with 95% confidence interval (CI) was used to demonstrate the association. The predictive power of serum latictic acid level for in-hospital death was evaluated through receiver operator characteristic curve, which generated C-statictic. A combination model was further constructed by adding serum latictic acid level to the Global Registry of Acute Coronary Events (GRACE) risk score (LA-GRACE risk score). The linear dependence between serum lactic acids level and othe clinical variables was analysed using Spearman rank correlation. Results: Of the 302 patients enrolled in the current analysis, 15 (5.0%) died during hospitalization. Serum lactic acid level (OR=1.657, 95% CI: 1.115 to 2.463, p=0.012)and left ventricular ejection fraction (OR=0.858, 95% CI: 0.767 to 0.959, p=0.007) were the only two independent predictors of in-hospital death. The C-statistic of serum lactic acid level for predicting in-hospital death was 0.886 (95% CI: 0.793 to 0.979). The LA-GRACE risk score improved the C-statistic of the GRACE score from 0.898 to 0.911 (p=0.294), with continuous net reclassification improvement of 0.567 (p=0.023) and integrated discrimination improvement of 0.206 (p=0.003). High serum lactic acid level was also asscoiated with larger enzymatic infarct size (p=0.002) and MACE (p=0.004). Further, it significantly correlated with white blood cell counts (r=0.264, p<0.001), serum creatinine level (r=0.189, p=0.001), and systolic blood pressure (r=−0.122, p=0.034). Conclusion: Serum lactic acid level on admission is asscoiated with poor myocardial perfusion and in-hospital outcomes in patients with acute myocardial infarction undergoing pPCI. It may contribute to better risk stratification in these populations. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This study was supported by the National Program on Key Basic Research Project of China (Grant No: 2019YFC0840601 and 2014CBA02003), National Natural Science Foundation of China (Grant No: 81870267, 81970295, 81521001, 81670318 and 81570314), Grant of Shanghai Shenkang on Key Clinical Research Project (Grant No: SHDC2020CR2015A and SHDC12019104), Grant of Shanghai Science and Technology Committee (Grant No: 19MC1910300, 18411950200 and 20JC1410800), Key Medical and Health Projects of Xiamen Province (No: 3502Z20204004), Grant of Shanghai Municipal Commission of Health and Family Planning (Grant No: 2017YQ057), Grant of Zhongshan Hospital Affiliated to Fudan University (Grant No: 2018ZSLC01), VG Funding of Clinical Trials (2017-CCA-VG-036) and Merck Funding (Xinxin-merck-fund-051).